Building Systemic Integrity: An Analysis of Learning Materials and Evaluations in Anti-Corruption Education in Elementary School - Suyitno, Suyitno; Retnasari, Lisa; Wardani, Ella Kusuma (International Journal of Educational Management and Innovation, 2026)
Background. Anti-corruption education is one strategic way to cultivate excellent generations who hold onto the values of honesty, responsibility, and social awareness from an early age. To instill these values, it is necessary to provide systemic reinforcement by developing more structured teaching materials and learning evaluations at elementary schools. The research aims to describe the systemic reinforcement of anti-corruption education through the development of materials and learning evaluation in SD Muhammadiyah Kayen, Yogyakarta. Methods. The research employed qualitative descriptive methods, including direct observations, in-depth interviews, and documentation, to collect data. Results. The results showed that schools have integrated anti-corruption teaching materials into several subjects, especially those included in Al Islam Kemuhammadiyahan. However, they are implicit and have not been included in the standardized curriculum structures. Besides, the learning evaluation has not been systematically designed to measure students' knowledge, attitudes, and anti-corruption values. Conclusion. Hence, the research recommends developing contextual anti-corruption teaching materials and learning evaluation instruments based on anti-corruption characteristics. The research novelty lies in the explicit integration of anti-corruption materials into the elementary school curriculum and the development of an anti-corruption character-based evaluation to systematically measure students' knowledge, attitudes, and anti-corruption values.